Liver specific gene immunotherapies resolve immune suppressive ectopic lymphoid structures of liver metastases and prolong survival. (October 2017) - Goodwin, Tyler J.; Shen, Limei; Hu, Mengying; Li, Jingjing; Feng, Richard; Dorosheva, Oleksandra; Liu, Rihe; Huang, Leaf
Abstract: The ability to generate potent immunotherapies locally and transiently for the treatment of cancers is a promising strategy to improve efficacy and decrease off-target toxicities. Here, we explored an alternative approach for the delivery of immunotherapeutic agents, in which we deliver the pDNA of an engineered PD-L1 trap and/or CXCL12 trap to the nucleus of liver hepatocytes via a lipid calcium phosphate nanoparticle. This strategy greatly increased the concentrations of immunotherapeutic agents in the local tissue, allowing the therapy to inhibit the accumulation of immune suppressive cells and liver metastasis. Furthermore, we find that the lipid calcium phosphate nanoparticles containing the pCXCL12 trap resolved the formation of immune suppressive ectopic lymphoid structures, while the pPD-L1 trap promoted T-cell survival and migration into the liver following vaccination against tumor antigens (>180% increase in survival). This approach showed superior efficacy in the treatment of the liver metastasis compared to free protein immunotherapies. This strategy should be considered as an approach to support liver metastasis therapies as well as for future research interested in manipulating the chemokine/cytokine immune factors within the liver. Significance: Our approach results in transient liver specific expression of gene immunotherapies with improved efficacy and reduced off-target toxicities over traditional systemically administered immunotherapies. This approach would allow clinicians to manipulate the liver and immune microenvironment to resist cancer invasion, improve organ health, and prolong patient survival.